Penyusunan Model Laporan Keuangan Entitas Mikro Kecil Menengah Berdasarkan SAK EMKM pada EMKM Konveksi - Nada Aulia Pertiwi; Hendi Rohendi; Setiawan Setiawan (Universitas Ma'soem, 2020)
This study aims to know the knowledge of EMKM Convections jeans in Soreang District regarding SAK EMKM, to find out the financial records carried out by EMKM, and to compile a model of EMKM Convection’s financial statements that are under SAK EMKM. In data collection, used snowball sampling and data analysis techniques are carried out through the stages of data reduction, evaluating EMKM’s knowledge of SAK EMKM, evaluating the suitability of the records carried out by EMKM Convection with applicable standards, namely SAK EMKM, seeing the similarity of activities contained in EMKM convection to create a model suitable for all EMKM convection and compile a model of financial statements for EMKM Convections following SAK EMKM. The results showed that the EMKM Convections in Soreang District still did not know about the existence of SAK EMKM, EMKM actors also still did a simple recording, there was no further record up to the preparation of financial statements. Besides, this study also produced a financial statement model for EMKM convections that were by the SAK EMKM.